Polity, policy and destination management: an exploratory study of political systems and management of tourism with special reference to the GCC countries. (2016) - Upadhya, Amitabh
Tourism, the dynamic and viable industry that it is, remains majorly dependent upon the adoption of an approach to strategic planning and formulation of policies for achieving successful destination management. This study hypothesises upon the concept that the political system of a country influences its structure of tourism governance and tourism development policies. The study investigates and analyses the nature and structure of tourism governance in the six Gulf Cooperation Council (GCC) countries namely, Saudi Arabia, United Arab Emirates, Oman, Qatar, Kuwait and Bahrain besides a few more for a comparative analysis. The study examines the role of state in developing and nurturing tourism in the light of tourism development policies within their respective countries. This is an exploratory study combined with case studies, used for analysing governance of tourism in the selected countries. The study notes that political environment of a country plays a major role in management of tourism.